Some Notes on Predication - Pinzani, Roberto (E-theca OnLineOpenAccess Edizioni, 2025)
In the Categories Aristotle defines the analytic relationship of ‘being said’ in terms of ordinary categorical predication. The interpreters found themselves facing different interpretative problems, among others the meaning of categorial terms, how to understand the predication relation or the predication relations, what properties these relations have, etc. In the present brief contribution I consider two questions concerning transitivity and the metaphysical meaning of Aristotelian definitions.